2016
DOI: 10.1371/journal.pone.0166389
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Attitudes among Early Adopters of Emerging Health Technologies

Abstract: IntroductionAdvances in health technology such as genome sequencing and wearable sensors now allow for the collection of highly granular personal health data from individuals. It is unclear how people think about privacy in the context of these emerging health technologies. An open question is whether early adopters of these advances conceptualize privacy in different ways than non-early adopters.PurposeThis study sought to understand privacy attitudes of early adopters of emerging health technologies.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Such inconclusive and contradicting findings may indicate that older adults had a lack of understanding of potential privacy implications. Uncertainties around privacy implications for emerging technologies were frequently identified themes among older adults [ 49 , 50 ]. Despite the uncertainties over privacy implications, older adults are willing to share information and compromise privacy when the technology is perceived as beneficial [ 17 ], improve or maintain independence [ 51 ], and valuable [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such inconclusive and contradicting findings may indicate that older adults had a lack of understanding of potential privacy implications. Uncertainties around privacy implications for emerging technologies were frequently identified themes among older adults [ 49 , 50 ]. Despite the uncertainties over privacy implications, older adults are willing to share information and compromise privacy when the technology is perceived as beneficial [ 17 ], improve or maintain independence [ 51 ], and valuable [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some earlier studies have also investigated the motivations and attitudes of individuals toward DTC-GT and genetic and genomic data sharing (Ball et al 2014;Brown Trinidad et al 2010;Cheung et al 2016;Critchley, Nicol, and Otlowski 2015;Lemke et al 2010;McGuire et al 2008;Oliver et al 2012;Vayena 2014;Wallis, Rolando, and Borgman 2013), this is the first study to interview individuals who have decided to share their data publicly without any institutional oversight. We analyzed the interviews by thematic coding analysis, and merged ideas topically (Thomas 2003).…”
Section: Discussionmentioning
confidence: 99%
“…While it might be assumed that early adoption of health technologies is coupled with a disinterest in privacy, a qualitative study of privacy attitudes among early adopters of personal wearable sensors and health apps demonstrated that members of this group placed a value on personal data privacy and expressed the desire to control their personal data. 31 Such findings underscore the importance of notification about data uses and consent in maintaining relations of trust when asking for personal health information.…”
Section: Continued Importance Of Informed Consent In the Age Of Mhealthmentioning
confidence: 98%
“…Studies of attitudes toward data sharing indicate that people prefer to be asked for permission to use their data in research, especially when health information is involved. 6,[28][29][30][31] A recent survey showed that 68% of users of digital self-tracking technologies said they would share personal health information "if privacy were assured" and 67% felt anonymity was "very" or "extremely" important. 6 Another survey found that respondents across generations were concerned about health privacy, 32 contrary to popular assumptions about millennial disinterest in privacy.…”
Section: Continued Importance Of Informed Consent In the Age Of Mhealthmentioning
confidence: 99%